Glycaemic response at night is improved after eating a high protein meal compared with a standard meal: A cross-over study. Issue 5 (May 2020) - Davis, Rochelle; Bonham, Maxine P.; Nguo, Kay; Huggins, Catherine E.
Summary: Background & aims: Eating at night, compared to day-time, results in a relative hyperglycaemia contributing to an increased risk of Type 2 diabetes for those who habitually eat at night, such as shift workers. Meal choice at night can adversely impact postprandial glycaemia. Meals high in protein have the capacity to favourably reduce night time perturbations in glucose. The aim of this study was to examine if a high protein meal attenuates postprandial glucose at night, compared with a standard protein meal. Methods: In a 2 × 2 factor cross over design, healthy adults completed four acute meal challenges. Test meals were consumed at 8am and 8pm on separate occasions; a high protein (HP) meal (41% of energy from protein, 29% from carbohydrates) or isocaloric standard meal (15% from protein, 46% from carbohydrate). Bloods were sampled at fasting and for three hours postprandially and incremental area under the curve (iAUC) determined using the trapezoid rule. Freidman's test was conducted prior to post hoc Wilcoxon sign test, and significance set at p < 0.0083 after Bonferroni correction. Results: Plasma glucose median (IQR) iAUC after the HP meal was similar to the standard meal when consumed in the morning (12.9 (19.9) vs. 36.4 (99.6)mmol/L.3 h, p = 0.028). The HP meal elicited a significantly lower glucose iAUC (59.6 (117.0)mmol/L.3 h) compared to the standard meal (208.8 (154.1)mmol/L.3 h) when consumed at night (p = 0.005). No significant differences in insulin responses were found between test meals, at either time of day (p = 0.100). Conclusion: A HP meal is effective in attenuating the postprandial glucose excursion observed with night eating by 71.4%, compared to a meal with a macronutrient composition within dietary guidelines. If eating at night, reducing the carbohydrate content of a meal, and replacing this with protein, can result in a more favourable postprandial metabolic response. Trial registration: Trial ID number: ACTRN12617000294358, Website of trial registry: http://www.anzctr.org.au/ . Highlights: Blood glucose is elevated at night compared to morning after eating the same meal. A meal higher in protein and lower in carbohydrate reduced night hyperglycaemia. Insulin responses at night were similar after a high protein and standard meal.